PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEOSCRIBE TERHADAP HASIL BELAJAR SISWA MATERI IKATAN KIMIA - Ismail, Ismail; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purposes of this research are to investigate:1) The differences in student learning outcomes between taught Videoscribe media and learning without Videoscribe  media in class X SMA Mujahidin Pontianak. on chemical bonding material 2) The influence of learning with  Videoscribe media the learning outcomes in class X SMA Mujahidin Pontianak on chemical bonding material. The form of the research was quasy experiment with nonequivalent control group design. Sample selection technique was random sampling. Instrument of the research was of test.  To find out the differences in student learning outcomes used the U-Mann Whitney test, based on the results of the hypothesis test obtained the value of Asymp. Sig. (2-tailed) of 0.033, the test  result showed that there was a difference between student learning outcomes taught Videoscribe media and student learning outcomes taught without Videoscribe. Learning using Videoscribe learning media in class X SMA Mujahidin Pontianak on chemical bonding material giving the influence of 19.85% toward  student learning outcomes.Keywords: Videoscribe learning media, learning outcomes, chemical bonds.